Exercise cardiac MRI-derived right ventriculo-arterial coupling ratio detects early right ventricular maladaptation in PAH. Issue 6 (22nd September 2016) - Lin, Aaron C.W.; Strugnell, Wendy E.; Seale, Helen; Schmitt, Benjamin; Schmidt, Michaela; O'Rourke, Rachael; Slaughter, Richard E.; Kermeen, Fiona; Hamilton-Craig, Christian; Morris, Norman R.
Exercise intolerance and right ventricular (RV) dysfunction are cardinal features of pulmonary arterial hypertension (PAH). Despite the significantly elevated afterload, patients rarely experience symptoms at rest until the late stages of the disease. Recent data suggest that the ability of the right ventricle to adapt to increased afterload is an important determinant of exercise capacity and outcome in PAH [1]. RV ejection fraction (RVEF) has been demonstrated to predict outcome [2]. There is also growing evidence that a noninvasively derived right ventriculo-arterial coupling ratio (VACR) may provide important prognostic information [3]. However, it remains unclear to what extent RV contractility is impaired during exercise and which metric best describes ventricular functional adaptation to afterload in PAH. We aimed to evaluate and compare the effects of submaximal exercise on RV systolic function and VACR in PAH and healthy subjects using cardiac magnetic resonance (MRI). We also examined and compared VACR and cardiopulmonary exercise test (CPET) in estimating the severity of disease. In well-compensated PAH, early RV maladaptation is best captured by changes in SV/ESV at exercise by cardiac MRI http://ow.ly/MyEi302UUeL